System of financial control and monitoring — a concept vision (Путеводитель предпринимателя, 2020)
In the conditions of world financial globalization the role and the importance of financial control and the monitoring representing a peculiar contour of modern system of state security increases. However at theoretical level questions of the organization of financial control and monitoring are poorly worked today, from our point of view the main reason for such situation consists in double interpretation of their functions and institutional registration.